Adnexal torsion-symptoms, diagnosis and management: a review of literature - Jain, Nidhi; Manchanda, Rahul; Chithra, Sravani; Lekhi, Anshika (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Adnexal torsion accounts for 3% of all gynaecologic emergencies. It consists of spectrum of pathologies including ovarian torsion, ovarian torsion with tubal torsion and isolated fallopian tube torsion. It usually presents with acute abdominal pain along with gastrointestinal symptoms such as nausea and vomiting. But due to presence of non-specific clinical features, diagnosis of adnexal torsion is a difficult task which requires high degree of clinical suspicion. Ultrasound with Doppler is helpful in its diagnosis. But even Doppler studies can miss the cases of adnexal torsion. So, laparoscopy is the gold standard for its diagnostic evaluation and simultaneous management. Conservative surgery should be preferred to preserve the future reproductive function. But in some cases such as infarcted ovaries, older women and suspicion of malignancy, adnexa may be required to be removed. Thus, prompt diagnosis and timely management of adnexal torsion is required to prevent the irreversible damage to adnexa. The authors here present a review of literature concerning the clinical features, diagnosis and management of adnexal torsion via a case series of six cases.